Photothermal treatment of oropharyngeal cancer with carbon-defective silicon carbide. Issue 26 (17th June 2021) - Mu, Haibin; Pang, Haiyang; Zheng, Ce; Wang, Kaixin; Hu, Narisu; Zhang, Bin
Abstract : Carbon-defective SiC1− x has been used for photothermal treatment of oral squamous carcinoma, which could meanwhile realize anti-wound infection. Abstract : Oral squamous carcinoma (OSCC) is a clinical common tumor with high recurrence rate and low 5 year survival rate. In this work, photothermal antitumor treatment has been performed to treat OSCC by taking anti-wound infection into consideration. By introducing C defects, we have successfully converted the semi-conductive SiC into metallic carbon-defective silicon carbide (SiC1− x ), and endowed it with the near infrared absorption property for photothermal therapy (PTT). The results revealed that SiC1− x mediated PTT treatment could remove solid OSCC tumor in a biosafe way, showing low hematotoxicity, cytotoxicity and tissue toxicity. Moreover, the low invasion of PTT treatment could not only prevent the invasion of bacteria, but also realize an antibacterial effect on the wound, both of which are important for oral surgery. SiC1− x could be excreted from the body post treatment, which thus reduces the long-term potential toxicity. On the whole, this study provided a promising way to treat OSCC in an effective and safe way.